Characterizing the Layer Structures of the Lacquerware From the Palace Museum by Terahertz Imaging in Reflection Geometry - Zhang, Hongfei; Zhao, Yuanmeng; Li, Chenyu; Zhang, Cunlin (Frontiers in Physics, 2021)
Chinese lacquerware is an important invention of arts and crafts in China. In this study a Chinese lacquerware is examined by terahertz reflectometric imaging. The lacquerware is a decorative work made of a wood panel covered with several layers of lacquers to depict motifs. In order to detect lacquerware, terahertz time-domain spectroscopic reflectometric imaging system was built by us. Here we have demonstrated that terahertz imaging system could highlight interfaces between layers in in a stratigraphic buildup in reflection geometry. It can be a versatile technique for obtaining structural information about lacquered objects, and contactlessly and non-invasively provide not only 2-D images but also subsurface 3-D images and stratigraphic images (b-scans). Utilizing terahertz time-domain spectroscopic reflectometric imaging system, we observe buried layers of the lacquerware, including the faults in the wood layer, and the lacquerware was not injured. Above results show that terahertz time-domain spectroscopic reflectometric imaging is a non-destructive inspection method for lacquerware and has great potential.